UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPS TERPADU SISWA KELAS VIII SMP NEGERI 2 JUNJUNG SIRIH KABUPATEN SOLOK MELALUI PENGGUNAAN MEDIA MIND MAP - Angra Melina (Universitas Batanghari Jambi, 2018)
Abstract This study aims to determine the use of mind map media is expected to increase the activity and learning outcomes of students of class VIII IPS Terpadu in SMP Negeri 2 Junjung Sirih Solok District. This type of research is Classroom Action Research (PTK). The object of this research is the students of class VIII consisting of 26 students. This research was conducted on November 22, 2017 - January 13, 2018. The study was conducted in two cycles, each cycle consisting of two meetings. At the time of the research, the researcher used observation sheet to see the activity change and the students' learning result during the learning process using mind map learning media. The data obtained is processed by percentage technique. Based on this research, it is found that with the use of mind map can improve the activity and the result of student learning but in the implementation still require the learning strategy and good class management.Keywords: Mind Map, Learning Activity, Learning Outcomes